Recurring submandibular haematoma revealing an angiosarcoma. Issue 2 (March 2015) - Mouallem, Guillaume; Khonsari, Roman Hossein; Gruffaz, Françoise; Bertolus, Chloé; Goudot, Patrick
Abstract We report the case of a 62-year-old patient who presented to our department with recurring haemorrhages six months after submandibulectomy for sialadenitis. Several local procedures had failed to control the bleeding. Secondary pathological examination led to the diagnosis of angiosarcoma. Angiosarcoma are extremely rare vascular tumours that exceptionally affect salivary glands. Most angiosarcoma have a quickly fatal outcome but the prognosis of oral angiosarcoma is better than skin and deep soft-tissue localizations. This is the first report of a submandibular angiosarcoma with documented imaging follow-up and histological confirmation. This case report emphasizes the importance of early diagnosis and indicates that recurrent bleeding after submandibulectomy is a red flag feature which can reveal a malignancy in exceptional cases.